Application of the PAKEM learning model to improve student learning outcomes in mathematics - Asri Ode Samura; Dadang Juandi (Journal of Didactic Mathematics, 2022)
This study examines the improvement of student learning outcomes using the Active, Creative, Effective, and Fun learning model. The application of the Active, Creative, Effective, and Fun learning model is closely related to other learning models. Active, Creative, Effective, and Fun learning models are helpful and can create meaningful learning. The research method used is classroom action research (CAR). This CAR research was conducted in two cycles. The research sample amounted to 22 people who were not taken at random. The data was obtained by using tests, namely the initial test, the first cycle test, and the second cycle test. They are calculating student completeness using the formula for individual mastery and classical wholeness and calculating the increase in learning outcomes using the N-Gain Normalized formula. Applying the Active, Creative, Effective, and Fun learning model can improve student learning outcomes in mathematics subjects as the subject of probability theory.